Inclusive Policy Innovation in Improving Welfare for People with Disabilities during the COVID-19 Period in Batam City - Sri Rahayu; Anggi Syahfitriani (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2022)
The purpose of this research is an effort to strengthen policies that must be carried out as a step in preparing regulations for the implementation of various policies, especially for people with disabilities, such as various breakthroughs in the development of basic competencies that include various skills. This research is motivated by the problems faced by the Batam City Government in fulfilling the right to work for people with disabilities and improving the welfare of people with disabilities. The theory used in this discussion refers to the Inclusive Policy Theory which is continuous with the Inclusive Economic Policy launched by the Ministry of Manpower, this research also uses qualitative methods with descriptive research types. The results of this study indicate that there are 5 challenges to the welfare of people with disabilities in Batam City, one of which is that there is no programmed job training for persons with disabilities. This means that people with disabilities find it difficult to find work and are unable to compete with workers who do not have physical disabilities. Therefore, inclusive policies and inclusive economies are able to coexist in advancing the economy of disabled workers and are accompanied by Law number 8 of 2016 in Article 53 paragraph (1).